RENDU-OSLER-WEBER DISEASE AT 75 YEARS OLD WOMAN - A. S. Barmenova; T. A. Bayesheva; N. S. Umbetalina; V. A. Suhova (SINAPS LLC, 2017)
The publication presents a clinical case of hereditary hemorrhagic telangiectasia in a woman of 75 years. In the first part of the article, literature data on the incidence and features of Rundu-Osler-Weber disease are presented, modern diagnostic principles based on the Curaçao criteria(1999) are reviewed, which allow to define the diagnosis as "reliable", with three criteria, "probable" - with Two criteria (most often the family nature of the disease and spontaneous nasal bleeding) and "doubtful", with one criterion of the above. Methods of treating hereditaryhemorrhagic telangiectasia are considered, the authors draw attention to the fact that the choice of the method of therapy depends on the degree of damage to the target organ. Symptomatic methods of treatment suggest slight relief for patients, but hereditary hemorrhagic telangiectasiaremains a progressive, severe and potentially life-threatening pathology. The second part of the article presents a clinical observation with late verification of the patient's P., 75 years of age. The data of medical history, including anamnesis, catamnesis, photographs of macro- andmicro-preparations are given. The presented observation illustrates the severe course of hereditary hemorrhagic telangiectasia, manifested by severe hemorrhagic syndrome, due to vascular malformations, the gradual involvement of internal organs in the pathological process with the formation of arteriovenous shunts, aneurysms. The manifestation of hereditary hemorrhagic telangiectasia in the described clinical case was manifested as abundant nasal, uterine bleeding, skin telangiectasias, followed by involvement in the pathological process of the lungs, organs of the gastrointestinal tract. The authors were able to observe a variant of the course and manifestation of visceral vascular anomalies. This clinical case illustrates the need to take into account the totality of all the symptoms of the disease in hereditary hemorrhagic telangiectasia for early detection of the disease, dynamic observation of the patient and the timely administration of therapy